EFFICACY OF CHICKEN MANURE AND PLANTS SPACING ON THE GROWTH AND YIELD OF GARDEN HUCKLEBERRY (Solanum scabrum) IN SARDAUNA LOCAL GOVERNMENT AREA, TARABA STATE - Waziri, Adamu Umar; Yusuf, A. (FUDMA Journal of Sciences, 2024)
Garden Huckleberry is an edible form of the common nightshade weed plant belonging to the family Solanaceae. The research was conducted in Sardauna Local Government, Taraba State. The objectives of the study were to determine the fertilizer (chicken manure) rate and spacing adequate for garden huckleberry cultivation. The experiment consists of three rate of chicken manure (0t/ha, 15t/ha and 20t/ha) with two spacing of 10cm×15cm and 15cm×20cm, with plots size of 0.75m² which was laid out in a randomized complete block design (RCBD) with three replications. The data were analyzed and presented using Figureical presentation. The result shows that chicken manure rate of 20t/ha, and 15×20cm spacing produced Huckleberry with highest number of leaves at 6 weeks after sowing among others. The researcher therefore, recommended that poultry manure at the rate of 20t/ha and the spacing of 15×20cm to be use by the farmers in huckleberry production for maximum yield.
Keywords: Chicken Manure; Plant spacing; Growth; Yield of Huckleberry